2005
DOI: 10.1073/pnas.0501181102
|View full text |Cite
|
Sign up to set email alerts
|

A central role of Arabidopsis thaliana ovate family proteins in networking and subcellular localization of 3-aa loop extension homeodomain proteins

Abstract: The organization of living cells is based on networks of interacting molecules. Systematic analysis of protein interactions of 3-aa loop extension (TALE) homeodomain proteins, fundamental regulators of plant meristem function and leaf development, revealed a highly connected, complex network. The network includes nine members of Arabidopsis thaliana ovate family proteins (AtOFPs), a plant-specific protein family, indicating a close functional connection to TALE homeodomain proteins. Evidence is provided that A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
293
0
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(308 citation statements)
references
References 35 publications
12
293
0
3
Order By: Relevance
“…For example, the mouse ZFs and homeoboxes 2 protein heterodimerizes with ZFs and homeoboxes 3, using the most N-terminal HD of both proteins (Kawata et al, 2003). In another example, the Arabidopsis ovate family of proteins has been identified as regulators of BELL and KNOX function by binding to their HDs and modulating their subcellular localization (Hackbusch et al, 2005).…”
Section: The Zf-hd Family Members Are All Florally Expressedmentioning
confidence: 99%
“…For example, the mouse ZFs and homeoboxes 2 protein heterodimerizes with ZFs and homeoboxes 3, using the most N-terminal HD of both proteins (Kawata et al, 2003). In another example, the Arabidopsis ovate family of proteins has been identified as regulators of BELL and KNOX function by binding to their HDs and modulating their subcellular localization (Hackbusch et al, 2005).…”
Section: The Zf-hd Family Members Are All Florally Expressedmentioning
confidence: 99%
“…Given the proposed role of KNOX in leaf proximal-distal patterning, we investigated genes that are DE in our data and are also bound and modulated by KN1 protein (Bolduc et al, 2012b). In Arabidopsis, BEL1-like homeodomain (BELL) proteins form heterodimers with KNOX proteins in combinations that determine target selection and subcellular localization (Bellaoui Smith et al, 2002;Bhatt et al, 2004;Hackbusch et al, 2005;Cole et al, 2006). Our data show that maize bel12 (GRMZM2G154641) is significantly upregulated in the preligule region, whereas bel14 (GRMZM2G125976) is expressed at low levels in the blade, moderate levels in the sheath, and most highly in the ligule region ( Figure 4G; Supplemental Table 4).…”
Section: Ligule Genes Are Expressed At Multiple Organ Boundariesmentioning
confidence: 99%
“…4 It has been shown that TALE proteins physically interact with each other and with members of the OVATE protein family in Arabidopsis thaliana. [5][6][7][8][9][10] These interactions have been shown to be important for localisation of homeodomain proteins to the nucleus and for DNA binding specificity. The complexity of the interaction network suggests functional redundancy within the TALE protein family and the possibility for compensatory interactions within the regulatory network.…”
Section: Introductionmentioning
confidence: 99%
“…The complexity of the interaction network suggests functional redundancy within the TALE protein family and the possibility for compensatory interactions within the regulatory network. 8 The Arabidopsis genome contains eight KNOX genes. The class I KNOX genes (STM1, BP/KNAT1, KNAT2, and KNAT6) are all expressed in the shoot meristem and play a role in shoot development.…”
Section: Introductionmentioning
confidence: 99%